Association between serum ligands and the skin toxicity of anti‐epidermal growth factor receptor antibody in metastatic colorectal cancer. Issue 5 (29th April 2015) - Takahashi, Naoki; Yamada, Yasuhide; Furuta, Koh; Nagashima, Kengo; Kubo, Akiko; Sasaki, Yusuke; Shoji, Hirokazu; Honma, Yoshitaka; Iwasa, Satoru; Okita, Natsuko; Takashima, Atsuo; Kato, Ken; et al.
<x xml:space="preserve">Abstract</x> Skin toxicity is a known clinical signature used to predict the prognosis of anti‐epidermal growth factor receptor (EGFR) antibody treatment in metastatic colorectal cancer (mCRC). There are no biological markers to predict skin toxicity before anti‐EGFR antibody treatment in mCRC patients. Between August 2008 and August 2011, pretreatment serum samples were obtained from KRAS wild‐type (WT) patients who received anti‐EGFR antibody treatment. Serum levels of ligands were measured by ELISA. A total of 103 KRAS WT patients were enrolled in the study. Progression‐free survival and overall survival of patients with a high grade (grade 2–3) of skin toxicity were significantly longer than those with a low grade (grade 0–1) of skin toxicity (median progression‐free survival, 6.4 months vs 2.4 months, P < 0.001; median overall survival, 14.6 months vs 7.1 months, P = 0.006). There were significant differences in distribution of serum levels of epiregulin (EREG), amphiregulin (AREG), and hepatocyte growth factor (HGF) between groups of low/high grade of skin toxicity (P < 0.048, P < 0.012, P < 0.012, respectively). In addition, serum levels of HGF, EREG, and AREG were inversely proportional to grades of skin toxicity as determined by the Cochran–Armitage test (P = 0.019, P = 0.047, P = 0.021, respectively). Our study indicated that serum levels such as HGF, EREG, and AREG may be significant markers to predict the grade of skin toxicity and the prognosis of anti‐EGFR antibody treatment, which contribute to improvement of the management of skin toxicity and survival time in mCRC patients.